The Effect Of Regular Direction Smash Drill Training On Smash Accuracy In Extracurricular Volleyball Players At SD Negeri 01 Bengkulu Tengah - Fikri, Al; Perdima, Feby Elra; Martiani, Martiani (UNIVED Press, Universitas Dehasen Bengkulu, 2025)
Physical Education is essentially an educational process that utilizes physical activity to produce holistic changes in individual quality, both in terms of physical, mental and emotional. At the educational level, especially in extracurricular volleyball activities in junior high schools, mastery of smash techniques is one of the main focuses of coaches in improving student skills. Many students still have difficulty in doing accurate smashes, even though they have enough energy. This study aims to determine the effect of Drill Smash training on the accuracy of Smashes in volleyball players at SD Negeri 1 Bengkulu Tengah. This study used a pre-experimental research design with one group pretest posttest design. The treatment was assessed by comparing the post-test with the pre-test (Dharma 2017:34). Based on the data analysis and discussion that have been presented previously, the following conclusions can be put forward: The drill training method has a significant effect on the volleyball smash of SD Negeri 01 Bengkulu Tengah Athletes, where the results obtained tcount> ttable = 2.21> 2.101. The results of the study, it can be concluded that the drill method has a significant influence on improving the volleyball smash skills of athletes at SD Negeri 01 Bengkulu Tengah. The t-test showing a t-value of 2.21 with a significance level of 0.000, less than 0.05, indicates that drill training carried out in a structured and intense manner contributes positively to improving the quality of the athletes' smash techniques.